Improvement of cloud stability, yield and β-carotene content of carrot juice by process modification. (October 2013) - Yu, Li Juan; Rupasinghe, HP Vasantha
This study investigated the effects of three processing factors, acid blanching, centrifugation and dynamic high pressure homogenization, on cloud stability of carrot juice. Results indicated that the optimum processing condition for stabilized carrot juice were with dynamic high pressure homogenization at 100 MPa combined with 2% citric acid blanching at 95–100 ℃ for 2 min followed by 2000 r/min centrifugation for 10 min. The improvement of juice yield was also investigated using a pre-treatment of three commercial enzymes: Pectinex 3XL® (pectinase), Celluclast 1.5 L® (cellulase) and Novozyme 188™ (β-glucosidase). The combination of 0.1 g/kg of Pectinex 3XL®, 0.1 g/kg of Celluclast 1.5 L® and 0.1 g/kg of Novozyme 188™ at 50 ℃ and pH 4.0 for 90 min was the most effective condition to improve carrot juice yield from 49% to 67%. The enzymatic treatment increased juice total soluble solids from 7.5 to 8.9°Brix and β-carotene content from 21.4 to 33.7 mg/kg.